2018
DOI: 10.1029/2017jc013619
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Change of Export Production at Xisha of the Northern South China Sea

Abstract: Physical‐biological interaction within the upper ocean influences fixed organic carbon with various efficiencies leading to spatial and temporal change of carbon export in the ocean, which is important for global biogeochemical dynamics but is inadequately understood in the northern South China Sea (NSCS). Here the temporal variations of primary and export production are investigated using a 1‐D physical‐biogeochemical coupling model at a pelagic station of Xisha (XS) in the NSCS. At this station, the model re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 45 publications
2
6
0
Order By: Relevance
“…Meanwhile, the upward advection brought up deep‐water nutrients to the euphotic zone to support an intense biological production in the NSCS during the late winter. These results are consistent with previous findings at two time‐series stations of the NSCS (Y. Chen et al., 2018; Li et al., 2015). Further model analyses suggested that higher nutrient advection of the NSCS during the late winter was caused by mesoscale eddies, due to the energetic cyclonic gyre in the NSCS with active eddy activities.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Meanwhile, the upward advection brought up deep‐water nutrients to the euphotic zone to support an intense biological production in the NSCS during the late winter. These results are consistent with previous findings at two time‐series stations of the NSCS (Y. Chen et al., 2018; Li et al., 2015). Further model analyses suggested that higher nutrient advection of the NSCS during the late winter was caused by mesoscale eddies, due to the energetic cyclonic gyre in the NSCS with active eddy activities.…”
Section: Discussionsupporting
confidence: 93%
“…These results are consistent with previous findings at two time-series stations of the NSCS (Y. Chen et al, 2018;Li et al, 2015). Further model analyses suggested that higher nutrient advection of the NSCS during the late winter was caused by mesoscale eddies, due to the energetic cyclonic gyre in the NSCS with active eddy activities.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Particulate organic carbon flux attenuation in the ocean interior is used to constrain the biological pump efficiency at a depth, i.e., the ratio of POC flux at each specific depth in the mesopelagic zone to that at the euphotic zone base (Martin et al, 1987;Buesseler et al, 2007;Chen et al, 2018). In this study, flux attenuation was used to express the variability of local biogenic POC (excluding soot and sediment-derived autochthonous POC) flux with depth in the study area.…”
Section: Application Of 210 Po-soot Coupling To Constrain Particulate Organic Carbon Export Fluxmentioning
confidence: 99%
“…A similar 1-D model approach was applied to explore the biophysical mechanism for the temporal change in the export production of the northwestern SCS (Y. Chen et al, 2018). However, since most 1-D models applied to the SCS omitted AD-N (Lu et al, 2017), the effects of AD-N on the regional planktonic dynamics have not been quantitatively verified yet.…”
mentioning
confidence: 99%